Integrating Local Culture into Biology E-Module: The Perceptions of Teachers and Students - Lathifah, Suci Siti; Ekowati, Ainiyah; Citra, Puspa; Chodijah, Siti (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2025)
Integrating local culture into science education is a strategic effort to enhance the relevance of learning to students' lives while fostering appreciation for regional heritage. In the context of biology education, incorporating culturally-rooted examples can make abstract concepts more tangible and relatable. This study investigates teachers’ and students’ perceptions of a digital biology e-module integrating golok tarisi local heritage within an Ethno-STEAM approach supported by Augmented Reality (AR). The module connects biodiversity, ecology, and sustainable resource use concepts with cultural practices. This research employed a mixed-method (qualitative–quantitative descriptive) design involving 16 biology teachers and 60 eleventh-grade students selected purposively. Data were collected through Likert-scale questionnaires, semi-structured interviews, and classroom observations, and analyzed using descriptive statistics and thematic analysis. Results show highly positive perceptions. A total of 87% of teachers considered the e-module highly relevant, and 82% found it easy to use. Among students, 85% reported increased engagement and 78% higher learning motivation. The e-module also supported digital literacy development through the use of multimedia and AR features, although 18% of teachers experienced technical challenges. Students reported improved conceptual understanding of biodiversity and ecological balance, supported by AR visualization of the golok tarisi production process. Observations confirmed increased interaction and critical thinking. The findings demonstrate that the Ethno-STEAM-based digital e-module is pedagogically effective and well-accepted by both teachers and students. It enhances engagement, learning motivation, digital literacy, and conceptual understanding of abstract biological concepts through AR-supported visualization. Despite minor technical constraints, the module fosters interactive, critical, and culturally meaningful biology learning. This study contributes to the development of contextual, interactive, and sustainable models for biology education.